Pengaruh Online Customer Review dan Promosi Terhadap Keputusan Pembelian Melalui Trust pada Produk Scincare Somethinc - Azzahra Raudia Ramdhani; Didy Ika Supryadi (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2026)
This study aims to analyze the effect of online customer reviews and promotions on the purchasing decisions of Somethinc skincare products with trust as a mediating variable among students of the University of Mataram. This study uses a quantitative approach with a causal associative design. Data were collected through a survey using questionnaires administered to 100 respondent’s selected using purposive sampling. Data analysis was conducted using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with the help of SmartPLS 3.0 software. The results of the study indicate that online customer reviews do not directly affect purchasing decisions but have a significant effect through trust. Promotion has been proven to have a significant effect on purchase decisions, both directly and through trust. In addition, trust has a significant impact on the purchase decision of Somethinc skincare products. These findings confirm that trust plays a strategic role as a mediating variable in strengthening the influence of online customer reviews and promotions on purchase decisions. This research is expected to serve as an academic reference and provide practical implications for skincare companies in designing marketing strategies based on consumer trust.